Understanding the Past to Support the Future: Linking Retrospective Childhood Attachment to Adult Perspectives on Caregiving - Sulaiman, Nabeela; Abbas, Saima; Javed, Asma; Mirza, Motasem; Nazim, Habiba; Tariq, Dur e Aden; Shahid, Raheela; Sipra, Fouzia Alam (Journal of Neonatal Surgery, 2025)
Background. Attachment theory, pioneered by Bowlby and Ainsworth, explains how early caregiver–child relationships form internal working models that influence socioemotional development across the life span. Secure, avoidant, ambivalent, and disorganized patterns shape later relational expectations, mental health, and caregiving orientations. Intergenerational research highlights how adults’ attachment representations, shaped by childhood experiences, influence their caregiving approaches, yet gaps remain in cultural contexts such as South Asia. Objective. This study examined how retrospective childhood attachment experiences influence caregiving attitudes among undergraduate students in early childhood education programs in Pakistan. The research aimed to (1) identify underlying factors in a retrospective attachment questionnaire, (2) explore recalled attachment figures and emotions, and (3) analyze participants’ views on causes of attachment issues and caregiving responses. Methods. A convergent mixed-methods design was employed with 165 students (97.6% female; mean age = 25.12). Quantitative data were collected through an adapted 17-item retrospective attachment questionnaire and analyzed using exploratory factor analysis. Qualitative insights were gathered from written interviews with 22 participants and examined through thematic analysis. Results. Factor analysis revealed four reliable dimensions: secure, anxious/preoccupied, dismissing, and fearful/avoidant attachment. Secure attachment emerged as the most endorsed style. Thematic findings indicated strong early bonds with mothers and siblings, fears centered on separation, and caregiving challenges linked to inconsistent care and neglect. Participants emphasized nurturing environments, open communication, and professional support as key caregiving strategies. Conclusion. Retrospective attachment recollections provide valuable insights into how early experiences shape adult caregiving orientations. Findings underscore both cultural influences and the practical implications for educators and healthcare providers in supporting secure attachment across generations